Penanaman Nilai-Nilai Budaya dan Karakter melalui Permainan Anak Tradisional pada Pendidikan Anak Usia Dini - Karoso, Subianto; Tri Cahyono, Budi; Pujosusanto, Ari; Handayani, Enie Wahyuning (Journal of Practice Learning and Educational Development, 2025)
This study aims to examine the role of traditional children's games in instilling cultural values and character development in early childhood. Traditional games used in Pendidikan Anak Usia Dini (PAUD) institutions serve as effective learning media to teach local cultural values and positive character traits. Through a literature review approach, the first step was to gather literature from various sources, such as academic databases, scientific journals, and digital libraries. The research findings show that games like congklak, petak umpet, kelereng, and engklek help children learn cultural values such as cooperation, mutual assistance, time management, and the importance of following rules. Furthermore, traditional games contribute to the development of children's character, including discipline, honesty, patience, and responsibility. Despite challenges such as a lack of understanding among teachers about traditional games and the influence of technology, this study recommends the importance of training for PAUD teachers, developing curricula that integrate traditional games, and innovating by combining technology with these games. This research offers valuable insights into the benefits of traditional games in early childhood education.